Sequencing analysis of OMI/HTRA2 shows previously reported pathogenic mutations in neurologically normal controls - Simón-Sánchez, Javier; Singleton, Andrew B (Human molecular genetics, 2008)
A novel heterozygous non-synonymous mutation and a novel polymorphism in OMI/HTRA2 locus have been associated with Parkinson's disease (PD) in a German population. In an attempt to replicate these results in an independent population, we analyzed the entire coding region of OMI/HTRA2 in a series of 644 North American PD cases with both young- and late-onset disease and in 828 North American neurologically normal controls. Our results show that neither of the variants previously related to PD were associated with PD in our cohort and that the risk variants were present in neurologically normal controls.